2017
DOI: 10.1002/jcop.21841
|View full text |Cite
|
Sign up to set email alerts
|

A Social Network Approach to Understanding Community Partnerships in a Nontraditional Destination for Latinos

Abstract: Cincinnati, like other new migration areas, has recently experienced tremendous growth in the Latino immigrant population. Because greater health disparities exist for Latinos compared to both majority and other minority groups, it is essential to understand how migratory patterns and healthcare infrastructure are related. In this study, social network analysis (SNA), which quantitatively assesses and evaluates network formation and network relationships, was used to investigate the structure of the Greater Ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…These included size, number of connections, cohesion (level of participation, density, and centralization), function (information sharing or referrals), and integration. 16,17,22,58-90 Eight studies identified organizations central to the network and/or network brokers (organizations serving as a bridge between other organizations) and characterized how those organizations positively contribute to network development. Another 5 studies identified and characterized sub-networks which included smaller groups of organizations within the overall network.…”
Section: Resultsmentioning
confidence: 99%
“…These included size, number of connections, cohesion (level of participation, density, and centralization), function (information sharing or referrals), and integration. 16,17,22,58-90 Eight studies identified organizations central to the network and/or network brokers (organizations serving as a bridge between other organizations) and characterized how those organizations positively contribute to network development. Another 5 studies identified and characterized sub-networks which included smaller groups of organizations within the overall network.…”
Section: Resultsmentioning
confidence: 99%
“…The structure of a social network includes relevant components and the patterns of interactions between these components. Analysis of the components and how they interact across the network can provide insight into how they relate to the broader community context, such as healthcare systems (Eiler et al 2017). SNA can also investigate intergroup contact across social structures and explore means to promote social integration.…”
Section: Social Network Analysis In Understanding Segregationmentioning
confidence: 99%
“…Fig. 11.3 (Hanneman and Riddle 2005;Eiler et al 2017). The SNA approach asserts that social life is rooted in the structure of social positions and relations between individuals.…”
mentioning
confidence: 99%
See 2 more Smart Citations